ESTIMASI KANDUNGAN KARBON ATAS PERMUKAAN TANAH PADA POHON DIKAWASAN HUTAN KOTA KABUPATEN KETAPANG - Adhitya, Pradana Wanda; Hardiansyah, Gusti; Yani, Ahmad (JURNAL HUTAN LESTARI, 2014)
The purpose of this research is to estimate above ground biomass and above ground carbon stock from the living trees without below ground carbon stock, necromass, litters and the soil carbon in the urban forest in Ketapang district and to see the spreading of carbon in the map view. The method that utilized is non destructive method, which using a combination between Landsat 7 ETM+ satellite imaginary and allometrics method to estimate the carbon stock. The urban forest in Ketapang district is fresh water swamp forests which have a big biodiversity of its flora and the fauna. The result of this research show that the urban forest have an enough big carbon stock especially carbon stock from the stem, the branch, and the leaf, and its total value is 6.216,26 ton C from the total 87,91 hectare of the vegetation areal in the urban forest have, its have a potential to sequestration of carbon as much as 18.202,91 ton CO2 equivalent, and from the total of carbon stock, we have known that the average of the carbon stock is 70,71 ton C/ha or its equal with its potension to absorb the carbon dioxide on the atmospheric as equal as 207,76 ton CO2 ha-1 equivalent. Keywords : Landsat, carbon, urban forest, biomass